Self-Regulated Learning and its Relationship to Monovision among Students of the College of Basic Education (College of Basic Education Research Journal, 2026)
The aim of the research is to identify: the level of self-regulated learning, the significance of the significant difference in the level of self-regulated learning according to the variable A- gender B- specialization, the level of monovision, the significance of the significant difference in the level of monovision according to the variable A- gender B- specialization, the significant correlation between self-regulated learning and monovision among students of the College of Basic Education. A random stratified sample of students of the College of Basic Education was selected, amounting to (1450). To verify the objectives of the research, the self-regulated learning scale prepared by (Madeed 2020) and the monovision scale prepared by (Abu Al-Joud et al. 2021) were adopted. After ensuring the validity and reliability of the two scales, they were applied to the research sample and the data were processed using the statistical package (spss). The following results were reached:Students in the College of Basic Education enjoyed a high level of self-regulated learning. Females had a higher level of self-regulated learning than males, and higher in the humanities than in the sciences.A higher-than-average level of monovision was observed among students in the College of Basic Education. Males had a higher level of monovision than females, and higher in the sciences than in the humanities.A significant positive relationship existed between self-regulated learning and monovision among students in the College of Basic Education.Based on the research results, several recommendations were made, includingBased on the research results, several recommendations were made, including:- University curriculum developers should emphasize the use of self-regulated learning by students, not just learning for the sake of earning a degree.- Counseling centers should provide workshops, seminars, and awareness-raising activities to encourage a multiplicity of perspectives and acceptance of others.Suggestions for future research were also presented, including:- The most common self-regulated learning skills among students and their relationship to certain variables, such as academic immersion and visual memory.- The effect of an educational program to transform students' cognitive styles from a single-perspective to a multi-perspective one.
Keywords: self-regulated learning; single-perspective; university students